Efficacy of Cone-Beam Computed Tomography in Evaluating Bone Quality for Optimum Implant Treatment Planning. Issue 3 (June 2017) - Liu, Jie; Chen, Huan-Yu; DoDo, Hamza; Yousef, Hadil; Firestone, Allen R.; Chaudhry, Jahanzeb; Johnston, William M.; Lee, Damian J.; Emam, Hany A.; Kim, Do-Gyoon
Abstract : Purpose: This study examined (1) if cone-beam computed tomography (CBCT) can determine relative differences in bone mineral density distribution using clinical images of patients' mandibular bone and (2) if the relative differences can be used to detect the effects of sex and age on bone mineral density distribution. Materials and Methods: Sixty-six clinical CBCT images from patients (36 females and 30 males) of 3 age groups (40, 50, and 60 years) were identified. Alveolar (AB) and basal cortical bone (CB) regions were digitally isolated. A histogram of gray levels, which are proportional to degrees of bone mineralization, was obtained from each region. Mean, variability (SD and coefficient of variation), and percentage differences of gray level parameters between AB and basal CBs were computed. Results: Significant sex differences in gray level variability were observed within the postmenopausal age group ( P < 0.042). Conclusion: These findings suggest that clinical CBCT images can be a valuable tool in providing information on bone quality, which is an important criterion for optimum planning for dental implant placement.